On the Maclaren River volcanic field: petrogenesis of Pleistocene Yakutat slab tear volcanism in south-central Alaska, (USA) - Bearden, Alexander Thomas (Kansas State University, 2023)
The Maclaren River volcanic field (MRVF) of south-central Alaska consists of at least three monogenetic volcanoes that lie along the projection of the ca. ~1 Ma Yakutat slab tear. These volcanoes, which are <1 Ma. lie along a ~20 km south-north transect within the Denali Gap, a region between the Aleutian and Wrangell Arcs previously considered to be amagmatic. In this study, I present results from geologic mapping, thin section petrographic analysis, whole rock major and trace element geochemical analysis, and Sr-Nd-Pb-Mg-B isotopic analyses of lavas and pyroclastic deposits of three MRVF volcanoes to document their physical volcanology and petrogenesis. Maclaren River volcanic field eruptive products (e.g., lavas and near-vent pyroclastic deposits) range from alkali basalt to subalkaline basaltic andesite and transitional basaltic trachyandesite/trachyandesite (~46-57 wt% SiO₂). The studied volcanoes are named #1, #2, #3, from north to south. Volcano #1 (ca. 958 ka) lavas are porphyritic and contain olivine phenocrysts in a groundmass of clinopyroxene + plagioclase ± sparse biotite microlites. Volcano #2 lavas and scoria are porphyritic and their mineralogy is indicative of a more hydrated mantle source (abundant phlogopite + amphibole + olivine + clinopyroxene phenocrysts) and show evidence of crustal interaction (granitic xenoliths). Volcano #3 is located ~9 km south of volcano #2, but erupted coevally at ca. 422 ka. At volcano #3, the rocks consist of olivine + clinopyroxene + plagioclase + opacitic amphibole and show evidence of crustal interaction (plagioclase + quartz xenocrysts). Sr-Nd-Pb isotopic analysis was conducted on a subset of samples from each MRVF volcano via thermal ionization mass spectrometry and multicollector inductively coupled plasma mass spectometry. ⁸⁷Sr/⁸⁶Sr[subscript i] values range from 0.70343-0.70401 and are similar to modern Aleutian and Wrangell Arc magmas and the Holocene, Buzzard Creek maars. This similarity is also borne out by Nd-Pb isotope data. All MRVF volcanoes display primitive mantle-like [delta]²⁶Mg values (-0.20 to -0.29). Volcanoes #1 and #2 display depleted mantle-like [delta]¹¹B values, while volcano #3 has a more positive [delta]¹¹B, suggesting influence from altered oceanic crust. I suggest the MRVF involves magma production in a subduction-affected environment, along a nascent slab tear (e.g., LILE enrichments, HFSE depletions, and adakite-like bulk rock chemistries). Batch melt modeling indicate three mantle sources for MRVF magmas: (1) a mantle wedge metasomatized by slab-derived sediment melt; (2) subcontinental lithospheric mantle also metasomatized by a slab-derived sediment melt; and (3) an eclogitic slab, where slab melts interacted with mantle peridotite. The magmas that formed volcano #1 are dominated by source #1, a metasomatized lithospheric mantle source. Volcano #2 is dominated by source #2, metasomatized subcontinental lithosphere, and volcano #3 is dominated by source #3, an eclogitic slab. This study provides further constraints on magma generation and mantle upwelling processes along flat slab tear/edge environments, as well as the tectonomagmatic processes that occurred at ~1 Ma in south-central Alaska, when the collision of the thickest (~30 km) segment of the Yakutat slab occurred.
Keywords: Maclaren River volcanic field; Petrogenesis; Magmatism